2014
DOI: 10.1246/cl.131222
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Regioregular Poly(3-substituted thiophene) Bearing Disiloxane Moiety in the Substituent. Remarkably High Solubility in Hexane

Abstract: Regioregular poly(3-substituted thiophene) derivative bearing pentamethyldisiloxane moiety at the 3-substituent is prepared by nickel-catalyzed polymerization reactions with dehydrobrominative or debrominative generation of the organometallic monomer. The monomer precursors 2-bromo-3-(4pentamethyldisiloxybutan-1-yl)thiophene (1a) and 2,5-dibromo-3-(4-pentamethyldisiloxybutan-1-yl)thiophene (1b) are prepared from 3-methylthiophene with 45 steps in overall good yields. Treatment of 1a with TMPMgCl¢LiCl at room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Mori and coworkers reported the synthesis of regioregular polythiophene derivatives having soft siloxane units in the side chains . Indeed, the films of siloxane‐containing polythiophenes showed 2 orders of magnitude smaller Young's modulus and 20 times higher elongation at break than P3HT.…”
Section: Introductionmentioning
confidence: 99%
“…Mori and coworkers reported the synthesis of regioregular polythiophene derivatives having soft siloxane units in the side chains . Indeed, the films of siloxane‐containing polythiophenes showed 2 orders of magnitude smaller Young's modulus and 20 times higher elongation at break than P3HT.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerization was carried out with standard Schlenk technique under a nitrogen or argon atmosphere. 1 H NMR (400 MHz), 19 F NMR (376 MHz) and 13 were purchased and used without further purification. Preparation of chlorobithiophene 4a and 4b was performed in a manner reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…Two remarkable peaks were observed in 2θ = 3.94° and 12.18°, respectively, as shown in Fig 2 (a). The result suggests that the thin film of the alternating copolymer 6c shows bilayer lamellar structure involving 7.3 Å and 22.4 Å distances, respectively, 13,29,30 (Fig 2(b)) The molecular modeling of the alternating copolymer 6c suggests the chain lengths of 11.6 Å and 2.2 Å, respectively. The values of the observed layer distances of copolymer 6c closely corresponds to the twice values 11.6 x 2 and 2.2 x 2 (Fig 2(c) In summary, we have shown that formal alternating thiophene−thiophene copolymers were synthesized when a differently-substituted halobithiophene was employed as a monomer by nickel-catalyzed deprotonative polymerization was applied.…”
mentioning
confidence: 94%
See 2 more Smart Citations